The handbook of global communication and media ethics - Fortner, Robert S.; Fackler, Mark. (Chichester, West Sussex, U.K. ; Wiley-Blackwell, 2011)
'This groundbreaking collection provides a comprehensive picture of the ethical dimensions of communication in a global setting. Bringing together scholars from around the world, this substantial work examines ethical issues raised by globalization, the practice of journalism, popular culture, and media activities, and provides the most detailed and diverse set of essays ever assembled on this vital topic. The editors, along with a team of international communication and media scholars, provides an authoritative overview of the philosophical and theoretical issues associated with global communication and media ethics, including examinations of feminism, ideology, social responsibility, reporting, metanarratives, blasphemy, development, and glocalism, among many others. In addition, the handbook includes international case studies addressing topics such as reporting, censorship, responsibility, terrorism, disenfranchisement, and guilt. The work includes contributions by several Islamic scholars discussing various facets of that religion's engagement with the public sphere, as well as essays dealing with the religious and cultural factors that complicate efforts to understand our world. Fortner and Fackler's innovative collection is both theoretical and practical, and will raise the ethical bar for both scholars and practitioners in the world of global communication and media'--
v. II : Problems of application / P. Mark Fackler -- Disenfranchised and disempowered : how the globalized media treat their audiences --a case of India / Anita Dighe -- Questioning journalism ethics in the global age : how Japanese news media report and support immigrant law revision / Kaori Hayashi -- Ancient roots and contemporary challenges : Asian journalists try to find the balance / Jiafei Yin -- Understanding Bollywood / Vijay Mishra -- Peace communication in Sudan : toward infusing a new Islamic perspective / Haydar Badawi Sadig and Hala Asmina Guta -- Media and post-election violence in Kenya / P. Mark Fickler ... [et a.] -- Ethics of survival : media, Palestinians, and Israelis in conflict / Oliver Witte -- Voiceless glasnost : responding to government pressures and lack of a free press tradition in Russia / Victor Akhterov -- Media use and abuse in Ethiopia / Zenebe Beyene -- Collective guilt as a response to evil : a case of arabs and muslims in the western media / Rasha A. Abdulla and Mervat Abou Oaf -- Journalists as witnesses to violence and suffering / Amy Richards and Jolyon Mitchell -- Reporting on religious authority complicit with atrocity / Paul Soukup -- The ethics of representation and the internet / Boniface Omachonu Omatta -- Authors, authority, ownership and ethics in digital media and news / Jarice Hansen -- Ethical implications of blogging / Bernhard Debatin -- Journalism ethics in a digital network / Jane B. Singer -- Now look what you made me do : violence and media accountability / Peter Hulm -- Protecting children from harmful influences of media through formal and nonformal media education / AsbjrnSimonnes and Gudmund Gjeltsen -- Ethics and international propaganda / Philip M. Taylor -- Modernization and its discontents : ethics, development and the diffusion of innovations / Robert S. Fortner -- Communication technologies in the arsenal of al Qaeda and Taliban : why the west is not winning the war on terror / Haydar Badawi Sadig, Roshan Noorzai, and Hala Asmina Guta -- The ethics of a very public sphere : differential soundscapes and the discourse of the streets / Robert S. Fortner.
Includes bibliographical references and index.
Keywords: Communication -- Moral and ethical aspects; Mass media -- Moral and ethical aspects